The F-Box Protein Rcy1p Is Involved in Endocytic Membrane Traffic and Recycling Out of an Early Endosome in Saccharomyces cerevisiae - Wiederkehr, Andreas (The Rockefeller University Press, 2000)

(untitled)
In Saccharomyces cerevisiae, endocytic material is transported through different membrane-bound compartments before it reaches the vacuole. In a screen for mutants that affect membrane trafficking along the endocytic pathway, we have identified a novel mutant disrupted for the gene YJL204c that we have renamed RCY1 (recycling 1). Deletion of RCY1 leads to an early block in the endocytic pathway before the intersection with the vacuolar protein sorting pathway. Mutation of RCY1 leads to the accumulation of an enlarged compartment that contains the t-SNARE Tlg1p and lies close to areas of cell expansion. In addition, endocytic markers such as Ste2p and the fluorescent dyes, Lucifer yellow and FM4-64, were found in a similar enlarged compartment after their internalization. To determine whether rcy1Δ is defective for recycling, we have developed an assay that measures the recycling of previously internalized FM4-64. This method enables us to follow the recycling pathway in yeast in real time. Using this assay, it could be demonstrated that recycling of membranes is rapid in S. cerevisiae and that a major fraction of internalized FM4-64 is secreted back into the medium within a few minutes. The rcy1Δ mutant is strongly defective in recycling.